Design Of Mathematical Model For Locomotion Control Of Snake-Like Robot - Bakar, Norhayati Abu (Universiti Sains Malaysia, 2017)
The snake-like robot has been widely developed in industries because it can move in the different and difficult path. The purpose of this thesis is to realize an asymmetrical locomotion in an unstructured environment. This is to imitate the natural snake locomotion where it is easier for them to adapt to any environment and place. The central pattern generator (CPG) control system with parameter transmitting characteristics is developed to control the asymmetric locomotion. The mathematical model has been designed in Matlab software to simulate the locomotion. In order to realize the snake asymmetric locomotion, the turning motion and round motion is studied based on the natural snake locomotion. The simulation is done by using Matlab software to control the snake robot locomotion. Some journal of researches which developed and modeling serpentine locomotion has been used as references. In this project, the CPG parameter is altered by giving bias to driving input or time constant as to obtain the desired asymmetric locomotion of the snake-like robot. The method of altering the CPG parameter of the snake-like robot is very useful for the robot to adapt to an unstructured environment. Simulation of the snake-like robot have been taken for the analysis of the locomotion control. Desired locomotion patterns can be achieved by adjusting the CPG parameters corresponding from the results.